Alternating current field controller for giant unilamellar vesicle electroformation chamber (Research, Society and Development, 2022)
The production of giant unilamellar vesicles, GUV has been the subject of many studies due to its simplicity and for mimicking essential complex functions of biological membranes. The production of GUVs is obtained by exposing lipid films to an aqueous solution in electric fields applied between two electrodes at a stable temperature, a process called electroformation. Controlling the field amplitude of electrodes immersed in the solution in the electroformation process is extremely important for the efficiency of the formation of GUVs to be used in training protocols for analysis for biomedical applications. The objective of this work will be to evaluate an automatic control method for the stability of the electric field amplitude in an aqueous solution. A control system based on a voltage-controlled attenuator and amplifier, VCA that uses pulse-width modulation, PWM to control the amplitude of the electric field was developed. The stability of the field amplitude over time was evaluated using an applied electric field with a frequency of 500 Hz and an amplitude of 600 mV RMS. The VCA control circuit prototype was tested as an actuator of a proportional-integral and derivative, PID control algorithm for a closed-loop control system of the applied field amplitude between two electrodes. Its performance was evaluated in saline solutions and pure water. The mean values of the field over time with PID control show a tendency to fall from the initial value of 0.3%. The proposed VCA control circuit proved to maintain field values over time effectively.